Developing Speaking Skill through Opinion Expression Method in Islamic Higher Education Context - Kuliahana, Ana; Marzuki, Abdul Gafur; Rustam, Rustam (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Through the Opinion Expressions Method, this study seeks to improve students' speaking skill in the context of Islamic higher education. It was separated into two cycles and planned as a cooperative classroom action research project. Data were gathered throughout six speaking lesson meetings during the second semester's term from class observations, field notes, questionnaires, and speaking tests. 24 students participated in the study. Based on the specified success criteria, the researchers determined how well the students were developing their speaking skill. According to the results, 11 students (48%) failed the first cycle while 13 students (54%) successfully completed it. The researchers carried on to the following cycle because the students’ speaking skill had not yet met the standards for success. Some changes were made to address the shortcomings in the First cycle, including: requiring more direction in structuring sentences by posing and responding to questions based on the callings in the photos provided in groups; encouraging students to be active in group work; emphasizing the importance of having fair distribution of work among the participants; and explaining that the direction-giving process should be improved. In the second cycle, 19 students (79%) successfully gained it, while just 5 students (21%) failed. Finally, a fascinating implication of this research was that the Opinion Expressions Method may be used to improve students' speaking skill.